Efeitos do canabidiol sobre comportamentos “tipo-compulsivo” em ratos: influências do sexo e do ciclo estral - Fabris, Débora dos Santos (2020)
Obsessive-Compulsive Disorder (OCD) is a severe and chronic psychopathology characterized by intrusive thoughts (obsessions) and ritualistic actions (compulsions). The neurobiology of OCD is not fully understood, and important differences in terms of prevalence, severity, and symptomatology exist between men and women. In addition, a significant percentage of patients are resistant to available treatments. Recent studies demonstrate the potential therapeutic use of a non-psychotropic compound, the cannabidiol (CBD), in mental disorders. The present study aimed to evaluate the effects of CBD in “compulsive-like” behaviors in rats, considering the influences of sex and estrous cycle phase in females. For this, male and female Wistar rats received intraperitoneal administration of CBD in doses of 0,3, 3 or 30 mg/kg or vehicle and had their behavioral responses analyzed in the open-field, marble burying, nestlet shredding, and spontaneous alternation tests. CBD had no significant effects on the behaviors assessed in the present study. Regarding the estrous cycle, in the open-field test, females during late diestrus showed greater expression of self-grooming behavior when compared to females in proestrus. In general, the results obtained indicate that CBD does not seem to have important effects on the “compulsive-like” behaviors evaluated. The effects of CBD in reversing "compulsive-like" behaviors induced by other manipulations should expand our understanding of the therapeutic potential of this compound in OCD.